Peripheral Giant Cell Granuloma Associated With Periodontal Intrabony Defect. Issue 3 (12th April 2019) - Moreno Rodríguez, Jose A.
Abstract : Introduction: The peripheral giant cell granuloma (PGCG) is associated with periodontal bony lesions in several situations and excision results in a soft papilla defect and an intrabony defect without soft tissue protection. Case Presentation: A PGCG associated with loss of periodontal support is described. Following the lesion excision, a specific flap design outlining a surgical papilla in the adjacent area was proposed. The aim of this flap design was to obtain an optimal condition for periodontal regeneration, to treat the lesion excision associated with soft tissue defect, and to avoid a second surgical area. Complete periodontal defect resolution without soft tissue contraction or lesion recurrence was obtained at 2‐year follow‐up. Conclusion: Early diagnosis and treatment are essential to prevent greater loss of periodontal attachment.